MARKETING STRATEGIES FOR INCREASING CUSTOMER ACQUISITION IN MURABAHAH FINANCING PRODUCTS - Mohammad Alief Hidayatullah; Riska Nuri Anggraeni (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to analyze marketing strategies to increase the number of customers for murabahah financing products at BMT Karanganyar Paiton. Murabahah financing is one of the leading products of Islamic financial institutions that plays a significant role in supporting the financing needs of the community, especially micro and small businesses. The research method used is a qualitative approach with field research. Data collection techniques were carried out through interviews, observations, and documentation related to marketing activities and the development of the number of murabahah financing customers. The results show that the marketing strategy implemented by BMT Karanganyar Paiton includes the implementation of a marketing mix that covers aspects of product, price, place, and promotion, as well as a personal approach to customers. This strategy is considered capable of increasing public interest and trust in murabahah financing products. However, there are several obstacles faced, such as limited human resources and low public understanding of Islamic financial products. This study concludes that an appropriate, consistent, and sharia-compliant marketing strategy plays a significant role in increasing the number of murabahah financing customers at BMT Karanganyar Paiton.